MINERALOGY AND GEOCHEMISTRY OF THE HEMATITE MUSCOVITE SCHISTS OF MALATYA, TURKEY: COULD IT BE THE FIRST KNOWN BANDED IRON FORMATION (BIF) IN THE TAURIDS AND ANATOLIA? - Sagiroglu, Ahmet; Kara, Hatice; Kurum, Sevcan (Carpathian Assoc Environment and Earth Sciences, 2013)
The Hematite Mica Schist (HMS) of Malatya outcrops as a thrust slice between the Permian Malatya Metamorphics and the Eocene Maden Complex and probably as a portion of the Neoproterozoic-Paleozoic Puturge Massif. The HMS is composed of laminae of quartz, mica-disthene (kyanite)-diopside -garnet and specular hematite. The Fe2O3 contents (>20 %) of the EMS and the Al2O3 contents (average 22 % are different from those of Proterozoic BIFs. The TiO2, K2O, MgO, CaO and Na2O contents are much higher than BIFs and average crust values, indicating detrital origin. Trace element and V. Sr, Y, Zr, Nb and Ba contents are higher than in BIFs. Total REE contents of the HMS are also much higher than those of BIFs of Proterozoic age, and the LREE concentrations are significantly higher than HREE concentrations, both of these indicators can be taken as evidence of detrital origin. Malatya HMS show strong positive Eu anomalies (Eu/Eu*=0.99-1.03) probably originating from a detrital feldspar contribution. The Ce anomalies (Ce/Ce*= 0.003-0.06) of HMS are low positive, indicating a low oxidation state. Data obtained from the studies suggest that the HMS was formed in glaciomarine settings (Raptian Type) with a low oxidation state, high detrital contribution, low or no hydrothermal contribution. Despite some contradictions in the geochemistry; the HMS show similarities to Raptian Type Neoproterozoic BIFs/IFs of Egypt and Saudi Arabia. As the cores of the Anatolian massifs are accepted northern margins of African/Arabian plate, the HMS may be related to the African/Arabian plate and their Raptian Type neoproterozoic iron formations. Banded Iron Formations (BIFs) are not known in Anatolian geologic environment, and the HMS of Malatya constitute evidence resembling Neoproterozoic BIF
Keywords: Hematite mica schist; banded iron formations; Neoproterozoic; Taurids-Turkey; Puturge Massif